Etika Konsumsi Muslim: Tanggung Jawab Moral dalam Boikot Produk Pro-Zionisme Berdasarkan Analisis Kaidah Fiqhiyah - Wafa Syahidah; Unang Fauzi (STIS DAFA MATARAM, 2025)
This article aims to analyze the moral responsibility of Muslims in boycotting pro-Zionist products through the perspective of qaidah fiqhiyah (Islamic legal maxims). The study employs a qualitative approach with a literature review method, focusing on the principles of qaidah fiqhiyah and their application in the context of ethical consumption. The findings reveal that qaidah fiqhiyah, such as